Effects of incubation temperature, inoculum size, and medium on agreement of macro- and microdilution broth susceptibility test results for yeasts. - Cook, R A (1990)
We examined the effects of temperature and inoculum on the agreement of macro- and microdilution broth MICs of five antifungal agents against six isolates of Candida species or Torulopsis glabrata. Incubation temperature affected results with amphotericin B, flucytosine, fluconazole, and SCH 39304, producing better agreement at 35 degrees C than at 37 degrees C. Agreement between methods was better with an inoculum size of 10(2) than with one of 10(4) yeast cells per ml in testing fluconazole or SCH 39304, and the discrepancies seen with a higher incubation temperature and a larger inoculum appeared to be additive. However, inoculum size did not seem to affect agreement between methods in testing amphotericin B, flucytosine, or ketoconazole. Regardless of test conditions, macrodilution broth MICs of amphotericin B for different isolates were strikingly higher than microdilution test MICs, with mean differences being greater than ninefold under some test conditions. We conclude that for most currently available antifungal agents, an incubation temperature of 35 degrees C and a starting yeast inoculum of less than 10(4) cells per ml improve the agreement between macro- and microdilution broth tests.